2011
DOI: 10.1021/nn1035872
|View full text |Cite
|
Sign up to set email alerts
|

Magnetophotonic Response of Three-Dimensional Opals

Abstract: Three-dimensional magnetophotonic crystals (3D-MPCs) are being postulated as appropriate platforms to tailor the magneto-optical spectral response of magnetic materials and to incorporate this functionality in a new generation of optical devices. By infiltrating self-assembled inverse opal structures with monodisperse nickel nanoparticles we have fabricated 3D-MPCs that show a sizable enhancement of the magneto-optical signal at frequencies around the stop-band edges of the photonic crystals. We have establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 40 publications
0
22
1
Order By: Relevance
“…For example, large Faraday and Kerr effects, as a result of the strong field localization in the magneto-optically active material, have been demonstrated in one-dimensional structures, such as a magnetic thin film sandwiched between dielectric Bragg mirrors [1] and magnetic/dielectric multilayer films at the edges of their photonic band gap [2,3]. A modification of the MO spectral response, especially prominent near the photonic band edges, was also observed in three-dimensional selfassembled inverse opal structures infiltrated with magnetic nickel nanoparticles [4]. Moreover, it has been shown that resonant Kerr effect can be obtained with subwavelength nanowire gratings made of MO dielectric materials, for a given polarization of the incident light, by tuning the incidence angle and grating parameters to operate near the resonant reflectance condition for the orthogonal polarization state [5].…”
Section: Introductionmentioning
confidence: 89%
“…For example, large Faraday and Kerr effects, as a result of the strong field localization in the magneto-optically active material, have been demonstrated in one-dimensional structures, such as a magnetic thin film sandwiched between dielectric Bragg mirrors [1] and magnetic/dielectric multilayer films at the edges of their photonic band gap [2,3]. A modification of the MO spectral response, especially prominent near the photonic band edges, was also observed in three-dimensional selfassembled inverse opal structures infiltrated with magnetic nickel nanoparticles [4]. Moreover, it has been shown that resonant Kerr effect can be obtained with subwavelength nanowire gratings made of MO dielectric materials, for a given polarization of the incident light, by tuning the incidence angle and grating parameters to operate near the resonant reflectance condition for the orthogonal polarization state [5].…”
Section: Introductionmentioning
confidence: 89%
“…The Kerr rotation and ellipticity were measured in a polar Kerr configuration at room temperature for wavelengths in the visible ( = 400 − 700 nm). Details of the magneto-optical method and equipment can be found elsewhere 29,30 . Spectra of ( ) and ( ) were recorded at room temperature by sweeping the wavelengths over the range of the visible in steps of Δ = 1 nm.…”
Section: Walther-meißner-institut Bayerische Akademie Der Wissenschamentioning
confidence: 99%
“…Magneto-optical (MO) materials have numerous high-end photonic applications in optical isolators and circulators, optical switches, high performance magnetic field sensors and satellite navigation systems [1][2][3][4][5][6][7][8][9][10][11]. Faraday rotation (FR) is one of the most important MO phenomenon, in which the applied magnetic field changes the polarization plane of propagating linearly polarized light by inducing a circular birefringence [1][2][3]7,12].…”
Section: Introductionmentioning
confidence: 99%